Local Curriculum in Nepal: Problems and Challenges in Development and Implementation - Adhikari, Sital (Dibyajyoti Journal, 2024)
The purpose of this article is to identify the issues and challenges seen in development and implementation of local curriculum. For this, as primary data, the education officers of the municipality, including the members of the local curriculum development committee, the principals and the teachers of the schools where the curriculum is Implements were taken as sample. The data is analyzed using descriptive style and qualitative research design. Secondary data is also used to fulfill the needs of this research. The challenges seen in curriculum development and implementation are mainly the lack of development of institutional mechanism and capabilities, the lack of competent and skilled human resources in local body, lack of commitment, lack of competent teachers, parents’ obsession with English language, not being able to explain its importance to parents’ others stakeholders, lack of trained teachers, absence of a body providing technical support required for curriculum development at the local level. Similarly, after development and writing the textbook, the publishers don’t want to print or publish it so the municipality has to print it with its own budget, just like that there is not any mechanism to monitor in school after implementing local curriculum etc are the issues and challenges of development and implementation of local curriculum.